NASUNIN, AN ANTIOXIDANT ANTHOCYANIN FROM EGGPLANT PEELS, AS NATURAL DYE TO AVOID FOOD ALLERGIES AND INTOLERANCES - Monica Gallo; Daniele Naviglio; Lydia Ferrara (European Scientific Journal, ESJ, 2014)
In recent years, the increasing use of synthetic dyes showed an increase of allergic contact dermatitis with tissues, food, pharmaceutical and cosmetic products. This paper describes a method for extracting quickly, efficiently and economically a natural dye the Nasunin, a purple anthocyanin. To assess the potential sensitizing effect on the skin, have been formulated and applied to the healthy skin of 58 volunteers, patch tests with haptens of the Italian Society of Dermatology, Allergology Professional and Environmental (ISDAPE or SIDAPA, in Italian) standard series, compared with patch tests containing Nasunin extracts. Of all the subjects tested, forty nine were negative to patch tests containg Nasunin, seven showed a positive reaction to irritative and two showed a positive reaction of probable allergic nature. Consequently, these preliminary data show that allergenic effects are negligible and thus the Nasunin could be used as colorant in textile, food, pharmaceutical and cosmetic fields. In particular, the results indicate that the Nasunin, used in concentrations lower than 1% is a natural dye harmless suitable to impart coloration, in addition, to its extraction from eggplant peels allows the recycling of waste products of the food industry.